2021
DOI: 10.1186/s13073-021-00956-1
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptomic subtyping of colorectal cancer liver metastases in the context of tumor heterogeneity

Abstract: Background Gene expression-based subtyping has the potential to form a new paradigm for stratified treatment of colorectal cancer. However, current frameworks are based on the transcriptomic profiles of primary tumors, and metastatic heterogeneity is a challenge. Here we aimed to develop a de novo metastasis-oriented framework. Methods In total, 829 transcriptomic profiles from patients with colorectal cancer were analyzed, including primary tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 46 publications
2
25
1
Order By: Relevance
“…Transcriptomic subtypes based on cancer cell-intrinsic signals have the presumed advantage of being applicable to both primary and metastatic tumors, without the need to adapt the classification approach. This was supported by PCA based on the ITH-low genes detected in this study and on the iCMS template genes, both showing intermingling of primary tumors and liver metastasis, which is in contrast to results based on unselected genes 41 . In further support of the appropriateness of intrinsic classifications for metastatic tumors, we did not observe any subtype depletions or shift in the distribution of iCMS classes between primary tumors and liver metastases.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Transcriptomic subtypes based on cancer cell-intrinsic signals have the presumed advantage of being applicable to both primary and metastatic tumors, without the need to adapt the classification approach. This was supported by PCA based on the ITH-low genes detected in this study and on the iCMS template genes, both showing intermingling of primary tumors and liver metastasis, which is in contrast to results based on unselected genes 41 . In further support of the appropriateness of intrinsic classifications for metastatic tumors, we did not observe any subtype depletions or shift in the distribution of iCMS classes between primary tumors and liver metastases.…”
Section: Discussionsupporting
confidence: 69%
“…Nonetheless, the profound phenotypic plasticity observed in at least a subset of patients challenges the potential reconciliation of subtyping schemes of primary and metastatic tumors, also of the congruent CMS proposed here. This supports the need for a de novo classification of metastases based on their in situ cellular states 41 .…”
Section: Discussionsupporting
confidence: 63%
“…Next, we investigated the correlation between the TLS enrichment gene signature and a previously proposed liver metastasis subtype (LMS) system recapitulated the main distinction between epithelial-like and mesenchymal-like tumors, with abundant immune and stromal component. 26 We found that TLS enrichment gene signature was significantly associated with LMS ( figure 2I , p<0.001), which showed that samples with LMS5 have a more favorable prognosis than those with LMS1 ( figure 2J ).…”
Section: Resultsmentioning
confidence: 82%
“…(2021), it is not well suited for the censored data (e.g., Freeman et al, 2022;Moosavi et al, 2021;Rebouillat et al, 2021). In our data, all observations are at least six while the missing values are smaller or equal to five, directly applying the traditional MF will yield inflated imputations as with other imputation methods.…”
Section: Mf Imputationmentioning
confidence: 92%
“…When applied to spatiotemporal data, the data can be formed as a matrix according to the spatial dimension and the temporal dimension. However, although MF imputation works well for imputing MAR spatiotemporal data in Huang et al (2013), Ranjbar et al (2015), and Yang et al (2021), it is not well suited for the censored data (e.g., Freeman et al, 2022; Moosavi et al, 2021; Rebouillat et al, 2021). In our data, all observations are at least six while the missing values are smaller or equal to five, directly applying the traditional MF will yield inflated imputations as with other imputation methods.…”
Section: Mf Imputationmentioning
confidence: 99%